OFR-76(2)-79 Development Of Highwall Mining Equipment (Phase I) Volume II - Mandius C. Lundal (The National Institute for Occupational Safety and Health (NIOSH), 1977)
This report describes the work done to develop a coal mining machine to increase productivity and recovery from thin seams beyond the highwall, in addition to decreasing the miner's susceptibility to to highwall hazards First, radar transducers were adapted to measure coal thinkness and detect rock and coal interfaces; Then, the radar was incorporated into a cutterhead with steering controls. Next, visual displays were designed to show cutter position in the coal seam, and anticipated change in coal seam inclination, Finally, development of a telemetry system made remote control of the cutterhead possible. Simultaneously, a high-performance extended depth (HPxD) auger machine was designed with an automatic system to handle 600 ft of 36-in, diameter dual spiral flight conveyor sections. A two man crew controls all operations from a weather conditioned cab outside the VDZ, either at night or day time. As a primary mining tool, working 4000 hr/yr (2 shifts/day) recovering 60% of the coal 600 ft beyond the highwall, productlon to 500,000 ton/yr can be achieved. Volume I provides an overview of machine, systems and productivity.